2015
DOI: 10.1590/1517-86922015210495716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elastic-band exercise on muscle damage and inflammatory responses in Taekwondo athletes

Abstract: Introduction: Elastic bands offer variable elastic resistance (ER) throughout a range of motion and their incorporation with exercise movements has been used for variable strength training and rehabilitation purposes. Objective: Investigate the effect of acute bout of progressive elastic-band exercise on muscle damage and inflammatory response in Taekwondo athletes (TKD) compared with untrained ones. Methods: Fourteen (TKD, n = 7 and untrained, n = 7) men performed 3 sets of progressive resistance elastic exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…All participants had no experience in resistance exercises of the wrist flexor muscles. Gadruni et al [23] found that muscle soreness and inflammatory markers indicative of muscle damage significantly increased 24h after the elastic-band exercise protocol in sedentary individuals. To our knowledge, the classic massage with peppermint oil and vaseline may have attenuated muscle soreness in the present study because massage supports blood and lymph circulation, and eliminates lactate accumulation by inflammation or fatigue following exercise [24].…”
Section: Discussionmentioning
confidence: 99%
“…All participants had no experience in resistance exercises of the wrist flexor muscles. Gadruni et al [23] found that muscle soreness and inflammatory markers indicative of muscle damage significantly increased 24h after the elastic-band exercise protocol in sedentary individuals. To our knowledge, the classic massage with peppermint oil and vaseline may have attenuated muscle soreness in the present study because massage supports blood and lymph circulation, and eliminates lactate accumulation by inflammation or fatigue following exercise [24].…”
Section: Discussionmentioning
confidence: 99%
“…Variable resistance (RV) corresponds to the change of intensity during the application of force training load, within the various variable resistances are intra-variable resistance, intra-repetition variable resistance, and intra-series variable resistance 44 . Some types of VR have reported increases in the indicators of muscle fatigue and inflammation in both athletes and sedentary people, evidencing increases in the DOMS and [La] 24 . On the other hand, VR protocols cause general and local fatigue in military athletes that is related to the increase in [La] (p < 0.001) and decreases in average power (p < 0.002) 1 .…”
Section: Variable Resistance and Muscle Fatigue Trainingmentioning
confidence: 99%
“…However, Miranda et al 55 , in the context of neural activation, stated that a 3-minute rest interval between series may represent a neuromuscular window between a state of fatigue and a state of the total recovery in trained women. These same researchers examined the effect of the different recovery periods (24,48, and 72 hours) between sessions of strength training using press banking in trained subjects. At the end, they concluded that a recovery period of only 24 hours induces an increase in [La] and RPE (p < 0.05) 56 , variables that are considered as indicators of muscular fatigue 35 and that are directly related to the decrease in performance 48 .…”
Section: Different Times Of Rest In the Training Of Strength And Muscmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been concluded that an increase in FRs results in MDA overproduction [5]. Cell membrane damage and muscle damage induced by FR attacks [6,7] increase the instability of cell membrane, which in turn increases creatine kinase (CK) and lactate dehydrogenase (LDH) releases into the bloodstream [8]. In this regard, it has been revealed that subjects with a greater increase in markers of muscle damage (i.e., CK and LDH) experience a more considerable increase in serum concentration after eccentric exercise [4].…”
Section: Introductionmentioning
confidence: 99%